PENGARUH PENAMBAHAN SARI WORTEL PADA YOGHURT DITINJAU DARI AW, KADAR AIR, VISKOSITAS, TOTAL ASAM TERTITRASI DAN KADAR PROTEIN - Dimas Fajar Nugroho; Desna Ayu Wijayanti (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2021)
Yogurt is a form of beverage product from milk processing that utilizes microbes (Streptococcus thermophillus and Lactobacillus bulgaricus.). In the fermentation process of fresh milk into a semi-solid emulsion product, yogurt also has high nutritional content, one of which is protein. and low in fat. The purpose of this study was to determine the optimal percentage of addition of carrot juice to improve the quality of yogurt in terms of water activity (AW), viscosity, total titrated acid and water content. The ingredients used are cow's milk, carrot juice and plain yogurt starter. Iodine, 75% alcohol and distilled water. The method used in this research is experimental method Comletely Block Design of 5 treatments, namely the addition of carrot juice to yogurt with a concentration of 0%, 10%, 15%, 20%, and 25%. volume of milk (1 liter), with each treatment repeated 4 times. Data analysis used ANOVA (Analysis of Variance), followed by Duncan's Multiple Range Test. The results showed that the addition of carrot juice to yogurt could increase the value of Aw: P0 (0.9) to P4 (0.96), water content: P0 (88.96%) to P4 (92.58%), the total acid value. titration: P0 (0.57%) to P4 (0.67%) and protein content value: P0 (2.97%) to P4 (4.89%), the viscosity value decreased from P0 (216.75) cP) becomes P4 (148.00 cP). Based on the research analysis, it can be concluded that the use of carrot juice with a concentration of 15% gives the best results for yogurt with a value of Aw (0.94), water content (91.21%), viscosity (177.75 cP), total acid titrated (0 , 65%), and protein content (4.26%).